Removal of lead ions from aqueous solution using phosphate‐based geopolymer cement composite - Chedly Tizaoui (Journal of Chemical Technology & Biotechnology, 2021)
BACKGROUNDWater contaminated by heavy metals has many negative impacts on human health and the environment. According to the UN's sustainable development goals, preserving natural resources will have positive impacts on living conditions by reducing diseases. In this study, a novel adsorbent synthesized from phosphate‐based geopolymer cement composite material was developed and evaluated for lead removal from aqueous solutions. The developed adsorbent is made from natural resources using a facile protocol, and thus it is suitable for both developed and developing countries.RESULTSAnalyses of mineralogical composition, pore‐size distribution and surface of the synthesized phosphate‐based geopolymer cement composite were performed. A microporous structure was observed from the microstructural characterization. Geopolymer cement was immobilized with sodium alginate to fabricate alginate–geopolymer cement beads (Alg/GES). The parameters influencing the adsorption process were investigated in batch mode. The obtained results showed that the adsorption capacity of Pb(II) ions increased with time and equilibrium was reached in 90 min. The optimum adsorption pH was 4.17. The experimental results showed that the adsorption equilibrium of Pb(II) on Alg/GES was well described by the Freundlich and Langmuir models whereas the adsorption rate was well fitted by the pseudo‐second‐order kinetics model. The maximum adsorption capacity obtained from the Langmuir isotherm was qmax = 0.38 mmol g−1. From the Dubinin–Radushkevitch isotherm model, the value of the free adsorption energy was 41 kJ mol−1.CONCLUSIONSCompared with other adsorbents, Alg/GES exhibited a greater adsorption capacity confirming that the phosphate‐based geopolymer cement can be suitable for removal of heavy metals from wastewaters.